Steroid therapy in swine flu: Beneficial or harmful - Krittibus Samui (Apollo Medicine, 2018)
H1N1 influenza virus is responsible for respiratory illness that may range from mild symptoms of common cold to severe disease on presentation that needs hospitalization and management in intensive care. Corticosteroids are used to treat disease of immunity, inflammation or salt, and water balance. Here, the role of corticosteroid in swine flu is reviewed in various literatures. It is found that result of corticosteroid use in the management of swine flu patients is unsatisfactory. Instead of benefit, it is potentially harmful. It causes to develop higher duration of hospital stay, prolonged mechanical ventilation and ultimately increased mortality.